PKM pengenalan wirausaha melalui keterampilan merajut pada anak Panti Asuhan Sejati Muhammadiyah Kota Makassar - Srikandi Srikandi; Siti Aisyah; Rosmiaty Rosmiaty (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of the Community Partnership Program (PKM) activities is to provide knowledge and skills for the children of the Muhammadiyah Sejati Orphanage in Makassar. The provided knowledge and skills are in the form of training in making souvenirs with knitting techniques. Targeted outputs are souvenirs in the form of hijab accessories and key chains. The provision of these skills is based on several problems in the Muhammadiyah Sejati Orphanage group namely: do not yet have the knowledge and skills about knitting. To achieve the success target of this Community Partnership Program the solution offered is to provide material with learning methods that are easily understood by the participants and accompany the participants as long as activities is on progress. The result of PKM is the enhanced knowledge and skills to recognize and practice direct knitting techniques, where they are directed at the creation of entrepreneurial-oriented objects.